A study of the dynamic progress of performances of prominent world-class-athletes in selected track and field events - Tilinger, P.; Kovar, P.; Hlavata, P. (Kinesiology, 2005)
The article presents the results of our studies on the dynamic progress of performances in track-and--field athletes in sprint, throwing and jumping. Prominent world-class athletes were followed and their performance developments in some events were analyzed and compared. In these groups some athletes were also investigated who had recently retired from competitive athletics. The investigation disclosed differences between sprinters, throwers and jumpers from the point of view of the beginning of specialized training, of the age in which they attained their top performances, and of the number of years of specialized training they needed in order to attain their top personal performances. It was also discovered that the sprinters started their specialized training as a rule at the age of 16 years and they attained their top performances between the ages of 24 - 25 years. In the case of throwers their beginning of specialized training was also at the age of 17 and their top performance came at 26 - 27 years; in the case of jumpers it was all a little earlier - beginning at 14 - 15 years of age and the top of performance between 23 - 24 years of age.